Mortality and morbidity of neck of femur fractures: A comparison between Orange and peripheral centres. (21st December 2015) - Marshall, Timothy; Suthersan, Mayuran; Chan, Mun Khin; Jenkins, Bridget; Toh, Mingzhou; Giddins, Vanessa; Jones, Evan
Abstract: Objective: The aim of this study is to examine and compare the mortality and morbidity of patients with neck of femur (NOF) fracture who presented initially to either Orange Health Service (OHS), a secondary orthopaedic referral centre or to a peripheral hospital and subsequently transferred to OHS. Design, setting and participants: This study is designed as a retrospective review of medical records of 151 patients with NOF fractures who were treated operatively between March 2013 and March 2014 at OHS. Patients were divided into OHS group and 'Other' group based on their initial presenting location. Main outcome measures: Mortality, unplanned intensive care unit/high dependency unit admissions, ischemic heart/cerebral events, infection rates and length of stay. Results: There was no statistically significant difference in mortality and morbidity proportions between both groups. There were significant differences between lengths of stay in the acute setting which was shorter in the 'Other' group. Conclusion: Contrary to the literature, this study found that the morbidity and mortality outcomes of patients with NOF fracture who presented initially to rural hospitals were equivalent to those who presented to a secondary orthopaedic referral centre. However, those who first presented to rural hospitals had a shorter duration of stay in the acute setting.